Periosteal osteoblastoma of the distal fibula with atypical radiological features: a case report. - Biazzo, Alessio; Armiraglio, Elisabetta; Parafioriti, Antonina; Confalonieri, Norberto (Acta Biomedica Atenei Parmensis, 2018)
We reported the case of a 22 year-old boy who suffered a periosteal osteoblastoma of the distal fibula. The radiographic features of our case did not correlate with the majority of periosteal osteoblastomas of the long bones reported in the literature and were identical to a periosteal aneurysmal bone cyst. Periosteal osteoblastoma is a very rare tumor with a wide range of clinical and radiological features, showing in 15% of cases association with secondary aneurysmal bone cyst. Radiologist and orthopaedic surgeon should be aware of the atypical behavior of this rare entity in order to avoid mistakes with other more common tumors arising on the surface of the long bones.